Numerical Modeling of One-Way Reinforced Concrete Wall Panels with Openings Strengthened with Carbon Fiber Reinforced Polymer (CFRP) - Qaddura M.J.; Ean L.W.; Mohammed B.S.; Ng C.Y. (Springer Science and Business Media Deutschland GmbH, 2025)
The research reported in this paper is based on a comparative numerical analysis between the FE analysis conducted on RC walls by Lima et al. [1] and the physical experiment by Mohammed et al. [2]. Seventeen one-way RC walls with eccentric (e = t/6) were modeled. Several opening sizes were used (5%, 10%, 20%, and 30% of the concrete body total area). The results of the nonlinear analysis revealed that all walls with all possible CFRP configurations exhibitedreduced deformation under load. The reduction percentage increases with opening size. On the other hand, the configuration of the CFRP affects the stress value and distribution, where CFRP sheets with 0 and 90 layout enhanced the maximum stress value by 5%. The strain value increased in areas far from the CFRP sheets and vice versa. The maximum strain occurred on the bottom corners of the openings, which explains the appearance of cracks in the concrete walls without CFRP. ? 2024, Institute of Technology PETRONAS Sdn Bhd.